Montmorillonite-norfloxacin nanocomposite intended for healing of infected wounds - García-Villén, Fatima (Int J Nanomedicine, 2019)
Background: Chronic cutaneous wounds represent a major issue in medical care and are often prone to infections. Purpose: The aim of this study was the design of a clay mineral-drug nanocomposite based on montmorillonite and norfloxacin (NF, antimicrobial drug) as a powder for cutaneous application, to enhance wound healing in infected skin lesions. Methods: The nanocomposite has been prepared by means of an intercalation solution procedure. Adsorption isotherm, solid-state characterization of the nanocomposite, drug loading capacity and its release have been performed. Moreover, cytocompatibility, in vitro fibroblast proliferation and antimicrobial activity against Pseudomonas aeruginosa and Staphylococcus aureus were assessed. Results: The clay drug adsorption isotherm demonstrates that the mechanism of NF intercalation into montmorillonite galleries is the adsorption as one single process, due to the charge–charge interaction between protonated NF and negatively charged montmorillonite edges in the interlayer space. Nanocomposite is biocompatible and it is characterized by antimicrobial activity greater than the free drug: this is due to its nanostructure and controlled drug release properties. Conclusion: Considering the results obtained, NF–montmorillonite nanocomposite seems a promising tool to treat infected skin lesions or skin wounds prone to infection, as chronic ulcers (diabetic foot, venous leg ulcers) and burns.